PEMBERIAN INSENTIF PPH ATAS KEGIATAN LITBANG UNTUK PENINGKATAN INOVASI DI INDONESIA - Fahrudi, Agung N.L.I; Ahmad, David; Onni Meirezaldi; Kartika P Kumalasari; Nurlita S Alfandia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Innovation has a role to recognize a central driver of economic growth and development even in countrylevel. The governments are now focusing on innovation ranking as part of their economic policy strategies.Economic fund the innovation progress to develop better nation and harmonize cooperation among thecountries. In this part, income tax incentives give a significant role for improving innovation throughresearch and development. However, the government commitment to support the innovation throughresearch and development is limited compare with the other countries. Therefore, Indonesia launchedregulation number 45 year 2019 ( Peraturan Pemerintah-PP Nomor 45 tahun 2019) about allocate theincome tax incentives for research and development. The paper addressed issue on PP Nomor 45 tahun2019 implementation in Indonesia and how far this regulation is needed. Global Innovation and ResearchDevelopment theory and Income Tax Review are the major theory used. It conducted in Qualitative Methodby using primary and secondary data. As a Result PP number 45 year 2019 is feasible to implement inIndonesia but there are several supporting regulation to give more clear information especially in verse 29C about income deduction from gross income for certain RnD in Indonesia.